Economic Impacts of a New Road Network in San-En Region, Japan: A Spatial Computable General Equilibrium Model - Yuzuru Miyata; Hiroyuki Shibusawa; Yasuhiro Hirobata; Akira Ohgai (European Regional Science Association (ERSA), 2006)
In this paper, we aim to evaluate impacts of a new road network on the regional economy in San-en, Japan. San-en area is a boundary region between Aichi and Shizuoka Prefectures where the industrial sector is concentrated. The regional economy in San-en strongly depends on the regional transportation networks. Recently, a new road construction is planned in the region. The efficiency of road investment is expected for the regional economy. We construct a spatial computable general equilibrium model to evaluate the border economy. The spatial economic impacts of a new road construction are analyzed by the numerical simulation under several scenarios.
Keywords: 330